2015
DOI: 10.1007/s11829-015-9379-7
|View full text |Cite
|
Sign up to set email alerts
|

The ecological role of extremely long-proboscid Neotropical butterflies (Lepidoptera: Hesperiidae) in plant-pollinator networks

Abstract: Extremely long proboscides of insect flower visitors have been regarded as an example of a coevolutionary arms race, assuming that these insects act as efficient pollinators for their nectar host plants. However, the effect of proboscis length on generalized or specialized flower use remains unclear and the efficiency of butterfly pollination is ambiguous. Neotropical Hesperiidae feature a surprising variation of proboscis length, which makes them a suitable study system to elucidate the role of extremely long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Borrell ; Johnson & Raguso ; Johnson et al . ; but see Bauder, Warren & Krenn ). Among hummingbirds, in contrast, handling trade‐offs may be large enough to lead to specialization and bill length matching tube lengths of flowers visited (Maglianesi et al .…”
Section: Phenotypic Specializationmentioning
confidence: 99%
See 1 more Smart Citation
“…Borrell ; Johnson & Raguso ; Johnson et al . ; but see Bauder, Warren & Krenn ). Among hummingbirds, in contrast, handling trade‐offs may be large enough to lead to specialization and bill length matching tube lengths of flowers visited (Maglianesi et al .…”
Section: Phenotypic Specializationmentioning
confidence: 99%
“…Long proboscides in bees and lepidopterans allow such species to obtain nectar from both short-and long-tubed flowers often without large tradeoffs (e.g. Borrell 2005;Johnson & Raguso 2016;Johnson et al 2017; but see Bauder, Warren & Krenn 2015). Among hummingbirds, in contrast, handling trade-offs may be large enough to lead to specialization and bill length matching tube lengths of flowers visited (Maglianesi et al 2014).…”
Section: P H E N O T Y P I C S P E C I a L I Z A T I O N M A Y N O T mentioning
confidence: 99%
“…Skippers play a central role in pollination ecology. Recent studies have shown that species with long proboscides feed significantly more often on flowers with long nectar spurs [ 24 ] and are non-pollinating nectar thieves [ 25 ], affecting the pollination success of flowers with purloined nectar. However, in some angiosperm lineages such as orchids, skippers appear to be important pollinators [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The proboscis of the Neotropical skipper Damas immaculata measured 52.7 mm, equivalent to more than twice the body length and represented the longest proboscis ever recorded in butterflies (Bauder et al, ). These insects with extremely long proboscides showed specialized feeding preferences on flowers with long nectar spurs in Costa Rica (Bauder, Warren, & Krenn, ). Furthermore, the feeding performance of 34 skipper species with varying proboscis lengths from a Costa Rican lowland rainforest area was assessed (Bauder, Morawetz, Warren, & Krenn, ).…”
Section: Introductionmentioning
confidence: 99%